Construal of self as a mental health inpatient: a systematic review and narrative synthesis of repertory grid studies - Wozniak, Eleanor Elizabeth; Hare, Dougal Julian; Gregg, Lynsey; Wittkowski, Anja (Frontiers in Psychiatry, 2025)
IntroductionMental health is influenced by how we perceive ourselves and others. A person’s conceptual structure and how he/she understands and makes sense of the world can be explored using the repertory grid technique (RGT), an assessment tool derived from personal construct theory. This review aimed to a) draw together relevant literature that had implemented the RGT to explore the conceptual system of a person diagnosed with a mental health condition necessitating psychiatric admission, b) synthesise research findings related to the structure and content of the conceptual system, and c) provide insights into how inpatient service users construed themselves and others to inform therapeutic practice.MethodsA systematic search of five electronic databases (MEDLINE, EMBASE, PsycINFO, CINAHL, and Web of Science) and thesis databases (EThOS and ProQuest), alongside manual searches in relevant articles and Google Scholar, was conducted. Included studies were appraised for methodological quality using the Quality Assessment Tool for Studies with Diverse Designs.ResultsTwenty-one studies were identified and analysed using narrative synthesis. Of these 21 studies, 12 intentionally used a comparison group and compared the conceptual systems of people with different mental health diagnoses or compared conceptual systems of people with and without a diagnosed mental health condition. Findings from comparison group studies suggested that the self-esteem of a person diagnosed with a mental health condition was lower, compared to a person with no identified mental health diagnoses. Other people were typically idealised by people experiencing mental ill health; however, this finding was not observed in the experience of depression. Cognitive complexity, conceptual structure, and construing were variable across mental health conditions. Conceptual structures that were “simple” and characterised by “tight” construing were consistent with the profile of people with a mental health diagnosis, except for people with schizophrenia spectrum and psychotic disorders.ConclusionsThe structure of a conceptual system differed in people with and without a mental health condition and across mental health diagnoses. Considerations for how the review findings could inform psychological therapy and suggestions for future research are offered.